2021
DOI: 10.22219/jk.v12i1.14077
|View full text |Cite
|
Sign up to set email alerts
|

Structural Model of Work-Life Balance Effect on Nurse Work Engagement

Abstract: Introduction: High job demands can cause problems for nurses, increased stress levels, burnout, and even turnover which results in decreased performance. Conditions of work-life balance that are not aligned may reduce work attachments. Objectives: to examine the structural model of the effect of work-life balance on work engagement. Methods: The research participants were 120 nurses, diploma graduates or nurses who were actively working in the field of nursing and living with their families. Data were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
0
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
0
0
3
Order By: Relevance
“…It means that the better HR management manages the work-life balance owned by each employee, the higher the employee's work engagement. This study results support previous researches on the relationship between work-life balance and work engagement which were conducted by Puspita (2021), Alisah et al ( 2020), Alvi et al (2014), Jaharuddin & Zainol (2019), Haar et al (2017), and Idulfilastri, et al (2021. These previous researches concluded that work-life balance has a positive and significant effect on work engagement.…”
Section: Work-life Balance Towards Work Engagementsupporting
confidence: 90%
“…It means that the better HR management manages the work-life balance owned by each employee, the higher the employee's work engagement. This study results support previous researches on the relationship between work-life balance and work engagement which were conducted by Puspita (2021), Alisah et al ( 2020), Alvi et al (2014), Jaharuddin & Zainol (2019), Haar et al (2017), and Idulfilastri, et al (2021. These previous researches concluded that work-life balance has a positive and significant effect on work engagement.…”
Section: Work-life Balance Towards Work Engagementsupporting
confidence: 90%
“…Sehingga work engagement menjadi sangat penting untuk diperhatikan dalam perkembangan perusahaan. Work engagement sebagai suatu keadaan motivasi yang positif dan pemenuhan kesejahteraan terkait pekerjaan (Blanch dan Aluja, 2009 dalam Wood et al, 2020) 2 . Schaufeli et al (2002) 3 mendefinisikan work engagement sebagai kondisi pikiran positif seseorang dan berkaitan dengan pekerjaannya, dicirikan dengan adanya vigor, dedication dan absorption.…”
Section: Aunclassified
“…Peneliti mengucapkan terima kasih sebesar-besarnya kepada seluruh pihak terkait yang telah membantu, mendukung, dan membimbing peneliti selama proses penyusunan penelitian hingga penelitian ini selesai. [2] Wood, J., Oh, J., Park, J., & Kim, W. (2020). The relationship between work engagement and work-life balance in organizations: A review of the empirical…”
Section: Acknowledgeunclassified
“…Penelitian yang dilakukan oleh Idulfilastri [13] dengan menggunakan 120 sampel perawat di Indonesia menghasilkan bahwa pengaruh work life balance terhadap work engagement berkontribusi sebanyak 8%. Sedangkan penelitian lain yang dilakukan oleh Wijaya dan Soejarto [14] dengan menggunakan 137 sampel karyawan Politeknik X di Yogyakarta menghasilkan bahwa pengaruh work life balance terhadap work engagement sebesar 41,2%.…”
Section: Aunclassified